Tectonostratigraphy of Banyumas Basin and Its Correlation to Petroleum Potential - Purwasatriya, Eko Bayu (2018)
Objective of this research is to understand tectonic event and stratigraphy in order to know better about petroleum potential of this area. Method used in this research is taking primary field data and combine with secondary data to interpret the results. The primary data of 841 shear fractures had been measured from the field in Banyumas basin, from various lithological formation such as Karangsambung Formation as the oldest, then Gabon Formation, Halang Formation, Kumbang Formation and Tapak Formation. The result is, there are 3 (three) paleostress from after Eocene to Pliocene age: (1) Paleostress NW-SE with transpressive or compressional strike-slip regime at after Eocene to Late Oligocene, (2) Paleostress NNW-SSE with pure strike-slip regime in Miocene and (3) Paleostress NNE-SSW with pure compressional regime in Pliocene. Generally, the paleostress is rotating clockwise, and stratigraphy of every tectonic events show an opportunity to the petroleum potential of this basin. Keywords: Tectonostratigraphy, Banyumas basin, Petroleum potential